Singularity analysis of cracks in hybrid CNT reinforced carbon fiber composites using finite element asymptotic expansion and XFEM. (April 2021) - Ebrahimi, S. Hamed
Abstract: The configuration of a crack with respect to the multi-material fiber reinforced composite joint determines the order of singularity of the stress solutions reproduced around the crack-tip. These solutions for different configurations of crack are obtained for carbon nano-tube (CNT) reinforced CFRP composite using an innovative finite element asymptotic analysis. Micro-cracks aligned with CNTs covered by interphase material in the reinforced polymer matrix (PMNC) may impinge upon the PMNC-Carbon fiber interface; and this investigation demonstrates that the CNT reinforcement increases the power of the stress field at the area surrounded by the crack-tip. Various CNT alignments have been considered with due concern on symmetric and anti-symmetric deviation of nanotubes on either side of the crack. The effect of notches is considered as well. Finally, the consistent singular mode shapes proposed are applies to efficiently increase the accuracy of the fracture analysis solutions for this category of orthotropic composite materials using a novel extended finite element (XFEM) approach named Direct-XFEM. Direct-XFEM reproduces the stress intensity factors (SIFs) directly, at a few additional degrees of freedom included in the local crack-tip area. The results indicate a notable improvement in contrast with the ordinary XFEM in the absence of the singular shape functions.